Application of Critical Path Method and Fuzzy Logic in Optimizing Bottled Drinking Water Production - Wanda Wira Yudiarti; Faiz Ainur Razi (InPrime: Indonesian Journal of Pure and Applied Mathematics, 2021)
AbstractProject management is one of the analytical techniques used for planning, scheduling, and making decisions about activities. This is useful so that the project can be implemented optimally and efficiently. Project management can be done by optimizing the network. Network optimization is very important for the production of bottled drinking water (AMDK) "AETA" produced by the PDAM of Kota Madiun. The optimization of the bottled water production network in this study uses the Fuzzy Critical Path Method (FCPM) analysis technique. Optimization of this fuzzy network is carried out to find a critical path in the production of bottled drinking water in order to get an efficient time in the production of 4 types of bottled drinking water, namely glass, 1.5L bottles, 600mL bottles, and gallons. The results showed that gallon product packaging has a high level of efficiency. In this research, fuzzy data analysis uses trapezoidal fuzzy numbers for bottled drinking water production time. Meanwhile, CPM is used to obtain the most efficient critical path or time in the AMDK production. The combination of these two methods is very helpful in project management so that the scheduling of activity can be run optimally.Keywords: Critical Path method; fuzzy; optimization; project management; scheduling. AbstrakManajemen proyek merupakan salah satu teknik analisis yang digunakan untuk perencanaan, penjadwalan, dan pengambilan keputusan tentang kegiatan. Hal ini bermanfaat agar proyek dapat dilaksanakan secara optimal dan efisien. Manajemen proyek dapat dilakukan dengan mengoptimalkan jaringan. Optimalisasi jaringan sangat penting untuk produksi Air Minum Dalam Kemasan (AMDK) "AETA" yang diproduksi oleh PDAM Kota Madiun. Optimasi jaringan produksi AMDK dalam penelitian ini menggunakan teknik analisis Fuzzy Critical Path Method (FCPM). Optimalisasi jaringan fuzzy ini akan dilakukan untuk mencari jalur kritis dalam produksi air minum dalam kemasan guna mendapatkan waktu yang efisien dalam produksi 4 jenis air minum dalam kemasan yaitu gelas, botol 1.5L, botol 600mL, dan galon. Hasil penelitian didapat pengemasan produk gallon memiliki tingkat efisien yang tinggi. Dalam penelitian ini, data fuzzy menggunakan bilangan fuzzy trapezoidal untuk waktu produksi AMDK. Sedangkan CPM digunakan untuk mendapatkan jalur atau waktu kritis yang paling efisien dalam produksi AMDK. Penggabungan antara dua metode ini sangat membantu dalam manajemen proyek sehingga penjadwalan suatu aktivitas bisa berjalan secara optimal.Kata kunci: Critical Path method; fuzzy; manajemen proyek; optimasi; penjadwalan.